Food and feast in premodern outlaw tales
1 online resource.
Keywords: "In Food and Feast in Premodern Outlaw Tales editors Melissa Ridley Elmes and Kristin Bovaird-Abbo gather eleven original studies examining scenes of food and feasting in premodern outlaw texts ranging from the tenth through the seventeenth centuries and forward to their cinematic adaptations. Along with fresh insights into the popular Robin Hood legend, these essays investigate the intersections of outlawry, food studies, and feasting in Old English, Middle English, and French outlaw narratives, Anglo-Scottish border ballads, early modern ballads and dramatic works, and cinematic medievalism. The range of critical and disciplinary approaches employed, including history, literary studies, cultural studies, food studies, gender studies, and film studies, highlights the inherently interdisciplinary nature of outlaw narratives. The overall volume offers an example of the ways in which examining a subject through interdisciplinary, cross-geographic and cross-temporal lenses can yield fresh insights; places canonic and well-known works in conversation with lesser-known texts to showcase the dynamic nature and cultural influence and impact of premodern outlaw tales; and presents an introductory foray into the intersection of literary and food studies in premodern contexts which will be of value and interest to specialists and a general audience, alike"--